Reduction of the PaO2/FiO2 Ratio in Acute Aortic Dissection: Relationship Between the Extent of Dissection and Inflammation - Aoyagi, Hideshi; Okishige, Kaoru; Isobe, Mitsuaki; Azegami, Koji; Ueshima, Daisuke; Maeda, Minetaka; Sugiyama, Koji; Shimura, Tsukasa; Kurabayashi, Manabu (Circulation Journal, 2010)
Background: Acute aortic dissection (AAD) often accompanies acute respiratory failure. The aim of this study was to clarify the relationship between the incidence of oxygenation impairment and the extent of distal type AAD. Methods and Results: A total of 49 patients with medically treated distal type AAD were retrospectively examined. AAD% was defined as the percentage of the volume of false lumen to that of aorta in the descending aorta. AAD% was measured by computed tomography. C-reactive protein (CRP) levels, white blood cell (WBC) counts, body temperature and arterial partial pressure of oxygen/fraction of inspired oxygen (PaO2/FiO2) ratio were measured serially. Oxygenation impairment was defined as a PaO2/FiO2 ratio ≤200. This occurred in 19 patients (39%). In patients with oxygenation impairment, AAD% (50.8±10.9% vs 28.0±11.9%, P<0.001), peak CRP levels (15.2±6.5 mg/dl vs 9.6±4.6 mg/dl, P<0.001), peak WBC counts (13,600±3,700 /μl vs 10,400±2,800 /μl, P=0.001) and body temperature (38.1±0.5°C vs 37.8±0.4°C, P=0.045) were higher than those without oxygenation impairment. It was found that there were inverse correlations between the PaO2/FiO2 ratio and AAD% (r=-0.604, P<0.001), and between peak CRP levels and the PaO2/FiO2 ratio (r=-0.635, P<0.001). Multivariate analysis demonstrated that the only independent predictor of oxygenation impairment was AAD% (odds ratio, 1.323; 95% confidence interval, 1.035-1.691, P=0.026). Conclusions: Respiratory failure in AAD appears to be closely correlated with the amount of aortic injury, possibly mediated by the magnitude of the systemic inflammatory reaction to the aortic injury. (Circ J 2010; 74: 2066-2073)